PENGARUH KUALITAS PRODUK, KUALITAS PELAYAN DAN HARGA TERHADAP KEPUASAN KONSUMEN TOKO AWI PANGKALPINANG - Suhendri; Panjaitan, Fery; Medinal (Jurnal Progresif Manajemen Bisnis, 2024)
This thesis, written and compiled by Suhendri with Student Identification Number 230200029, is titled "Analysis of the Effect of Product Quality, Service Quality, and Price on Customer Satisfaction at Toko AWI Pangkalpinang." Conducted from February 2024 to May 2024, the research spans 74 pages without appendices. The study aims to analyze the impact of product quality, service quality, and price on customer satisfaction at Toko AWI in Pangkalpinang. A quantitative research method with a survey approach was used, involving a sample of 50 respondents. Data were collected through questionnaires distributed to customers of Toko AWI. The data analysis technique employed is multiple linear regression to assess the influence of the independent variables (product quality, service quality, and price) on the dependent variable (customer satisfaction), processed using IBM SPSS Version 25. The findings indicate that product quality partially affects customer satisfaction, with a significance value of 0.000 < 0.05 and a t-value of 4.271 > t-table value of 1.679. Service quality also partially affects customer satisfaction, with a significance value of 0.000 < 0.05 and a t-value of 3.086 > t-table value of 1.379. Price has a partial effect on customer satisfaction as well, with a significance value of 0.000 < 0.05 and a t-value of 2.514 > t-table value of 1.679. Additionally, product quality, service quality, and price collectively affect customer satisfaction, with a significance value of 0.000 < 0.05 and an F-value of 56.327 > F-table value of 2.81